Réponses

2014-02-18T13:05:35+01:00
(9x+6)2+(9x+6)(7x-5)=(9x+6)(2+7x-5) =(9x+6)(2+7x-5)=(9x+6)(2-5+7x)=(9x+6)(-3+7x)                                                                                                                                                                                   on recopie les termes qui se ressemble     
merci mais enfaite c'est pas (9x+6)2+(9..... mais c'est (9x+6)[au carre]+(9x.... Désoler Merci
2014-02-18T14:56:01+01:00
(9x+6)²+(9x+6)(7x−5)   
=(9x+6)(9x+6+7x-5)
=
(9x+6)(16x+1)
=3(3x+2)(16x+1)